2015
DOI: 10.3390/rs70607029
|View full text |Cite
|
Sign up to set email alerts
|

Potential of VIS-NIR-SWIR Spectroscopy from the Chinese Soil Spectral Library for Assessment of Nitrogen Fertilization Rates in the Paddy-Rice Region, China

Abstract: Abstract:To meet growing food demand with limited land and reduced environmental impact, soil testing and formulated fertilization methods have been widely adopted around the world. However, conventional technology for investigating nitrogen fertilization rates (NFR) is time consuming and expensive. Here, we evaluated the use of visible near-infrared shortwave-infrared (VIS-NIR-SWIR: 400-2500 nm) spectroscopy for the assessment of NFR to provide necessary information for fast, cost-effective and precise fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…The wavebands near 2200 nm were significantly related to the frequency peaks of O-H and N-H. These wavebands were very important for predicting organic matter content so the prediction result for pH was similar to previous studies [ 34 ].…”
Section: Resultssupporting
confidence: 84%
“…The wavebands near 2200 nm were significantly related to the frequency peaks of O-H and N-H. These wavebands were very important for predicting organic matter content so the prediction result for pH was similar to previous studies [ 34 ].…”
Section: Resultssupporting
confidence: 84%
“…Partial least squares regression (PLSR) is a commonly used linear model; however, there are many nonlinear relationships between spectral data and target soil characteristics in nature [5,6]. Therefore, some non-linear machine learning techniques, including artificial neural networks (ANN), support vector machine regression (SVMR), least square-support vector machines (LS-SVM), random forest and the Cubist regression model (Cubist) have been used [7,8,9,10,11,12,13]. Moreover, soil is a complex mixture that consists of water, air, and organic and inorganic mineral matter of variable origins, so it is difficult to achieve universal acceptance with the same calibration techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near infrared (Vis-NIR) spectroscopy has been widely used in many sectors, including the food, material, and life sciences [7][8][9]. In the field of forestry, many studies have demonstrated its potential to determine components, such as moisture, density, lignin content, and so on; detect wood preservation; and classify species [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%